On the ability of a viscoelastic model to predict the average cyclic energy dissipated by a 3D layer-to-layer composite. (1st January 2023) - Navrátil, L.; Carrere, N.; Le Saux, V.; Leclercq, S.; Marco, Y.
Abstract: This article aims at providing a better understanding of the dissipative mechanisms activated in a 3D layer-to-layer composite under relatively low cyclic loadings. This is done by comparing the numerical and experimental dissipation responses of the investigated specimen under the so called heat build-up protocol. For this purpose, a finite element model based on micro-computed tomography results of the tested specimen was generated. The simulation/experiment comparisons show that the proposed generalised Maxwell model predicts well the average dissipation as long as the specimen is free of damage. In this regard, the first experimentally detected thermal events enable to highlight clearly the limits of the adopted modelling strategy.